The Effect of the Use of Nursing Process Conference Focusing on NANDA-I, NOC and NIC Classification in Adult In-patients Toward Quality of Nursing Note - โรจนดิษฐ รัตนาภรณ์; ตันสุวรรณรัตน์ กุลรัศมิ์; บุญญานุรักษ์ พวงรัตน์ (Journal of The Royal Thai Army Nurses, 2019)
This quasi-experimental research aimed to compare quality of nursing note before and after using nursing process conference model in adult patients developed by researchers based on the classifications of nursing diagnosis, outcomes and interventions which supported by concepts of critical and rational thinking within nursing profession for implementing nursing process evidenced by nursing note for individual patient written by 47 professional nurses. The sample was 500 nursing notes before and after experimentation which 250 notes of each were reviewed using reviewing form for nurse’s note quality developed by researchers based on concepts of the classification of nursing diagnosis, outcome and intervention which Alpha Cronbach was .75 and t-test indicated that means of total score and in each step of nursing process after experimentation on nursing note’s quality was significantly higher than before at .05. In addition, mean scores of nursing note quality after the experimentation in nursing assessment step was at high level, in nursing outcome and evaluation steps were at the lowest level. These results revealed that nursing note should be improved to indicate the use of completed nursing process along with the implementation of professional nursing languages that being internationally accepted. Then nursing notes in all health care service institutions should be systemically reviewed.